Habitat covariates do not artificially cause a negative correlation between native and non‐native species richness. (17th June 2021) - Beaury, Evelyn M.; Finn, John T.; Corbin, Jeffrey D.; Bradley, Bethany A.
Abstract: When analyzing biotic resistance/diversity‐invasibility, including predictors of species richness may result in a false negative correlation between native and non‐native richness. However, reanalysis of vegetation surveys shows that the negative effect of native richness is statistically significant whether or not predictors of species richness are included. Abstract : When analyzing biotic resistance/diversity‐invasibility, including predictors of species richness may result in a false negative correlation between native and non‐native richness. However, reanalysis of vegetation surveys shows that the negative effect of native richness is statistically significant whether or not predictors of species richness are included.